Analisis Pertumbuhan Mindi (Melia azedarach L.) dan Produktivitas Sorgum (Sorghum bicolor L.) Galur G55 dan BIOSS-04 dalam Sistem Agroforestri - Andhira Trianingtyas; Nurheni Wijayanto; Supriyanto Supriyanto (Jurnal Silvikultur Tropika, 2020)
needs was decreasing. So it needs a system that maximizes land one of them is agroforestry. Agroforestry will combine mindi tree (Melia azedarach L.) were 2 years old with a spacing of 2.5 mx 2.5 m, and agricultural crops is sorgum strain of SEAMEO BIOTROP development results that G55 is a BMR (Brown midrib) strain and BIOSS 04 which belonging in sweet sorghum. The research purpose is to analyze the growth of mindi on agroforestry systems and monoculture and analyze the growth and productivity of sorghum on agroforestry systems and monoculture. The results showed growth of mindi as high tree, diameter of stem, canopy and root diameter larger on agroforestry than monocultures. Growth and productivity of sorghum in the two strains showed lower on agroforestry cropping pattern. Sorghum G55 and BIOSS 04 strains can grow under mindi trees but can not produce optimally. Keywords: Agroforestri, Melia azedarach, Sorghum bicolor